2017
DOI: 10.1182/blood-2017-01-765107
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of hairy cell leukemia identifies novel recurrent genetic alterations

Abstract: Key Points• KMT2C mutations occur in 15% and 25% of patients with cHCL and vHCL, respectively, along with CCND3 and U2AF1 mutations each in 13% of vHCLs.• NF1, NF2, N/KRAS, and IRS1 alterations contribute to clinical resistance to vemurafenib treatment in patients with cHCL.Classical hairy cell leukemia (cHCL) is characterized by a near 100% frequency of the BRAFV600E mutation, whereas ∼30% of variant HCLs (vHCLs) have MAP2K1 mutations. However, recurrent genetic alterations cooperating with BRAFV600E or MAP2K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
118
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(131 citation statements)
references
References 28 publications
4
118
0
9
Order By: Relevance
“…Alterations of the cell cycle are essential in the pathology. In addition to the overexpression of cyclin D1, recurrent inactivation of the cell cycle inhibitor CDKN1B/p27 was identified in more than 10% of cases . Although TP53 mutations and/or del(17p) seem infrequent in HCL, it is recommended to assess TP53 status in case of PNA resistance .…”
Section: What Has Recently Improved Understanding Of Hairy Cell Leukementioning
confidence: 99%
See 1 more Smart Citation
“…Alterations of the cell cycle are essential in the pathology. In addition to the overexpression of cyclin D1, recurrent inactivation of the cell cycle inhibitor CDKN1B/p27 was identified in more than 10% of cases . Although TP53 mutations and/or del(17p) seem infrequent in HCL, it is recommended to assess TP53 status in case of PNA resistance .…”
Section: What Has Recently Improved Understanding Of Hairy Cell Leukementioning
confidence: 99%
“…In addition to the overexpression of cyclin D1, recurrent inactivation of the cell cycle inhibitor CDKN1B/p27 was identified in more than 10% of cases . Although TP53 mutations and/or del(17p) seem infrequent in HCL, it is recommended to assess TP53 status in case of PNA resistance . Inactivating KLF2 mutations were observed in 15% of HCL cases and 30% of marginal zone lymphomas (MZL) KLF2 is a transcription factor controlling the differentiation of multiple B‐cell subpopulations, including marginal zone B cells.…”
Section: What Has Recently Improved Understanding Of Hairy Cell Leukementioning
confidence: 99%
“…We reported that HCL expressing unmutated (>98% homology to germline) immunoglobulin heavy-chain variable (IGHV) rearrangement type IGHV4-34 expresses wild-type BRAF and has a poor prognosis like HCLv, whether immunophenotypically consistent with HCLv or HCL [12,13]. Mutations within MAP2K1 encoding MEK1 have been found in HCLv and IGHV4-34+ HCL [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to HCL, CCND3 mutations were identified in 13% of HCL‐V cases,23 a frequency that is identical to that observed in SMZL and less than the 25% of SDRPL cases 24, 26…”
Section: What Has Recently Improved the Understanding Of Hcl And Hcl‐mentioning
confidence: 74%